Bleeding Complication of Triple Therapy of Rivaroxaban, Prasugrel, and Aspirin: A Case Report and General Discussion. (11th March 2014) - Gruenebaum, Dane D.; Alsarah, Ahmad; Alsara, Osama; Laird-Fick, Heather
Abstract : Hemorrhagic side effects are the bane of oral anticoagulation. Despite careful selection of medications and close monitoring, some adverse events are unavoidable. The available literature about the risks of triple oral anticoagulation therapy versus dual antiplatelet therapy does not address all of the medication combinations currently available. This report describes a patient with atrial fibrillation and recent stent placement who developed severe, recurrent epistaxis on aspirin, prosugrel, and rivaroxaban. We believe this is the first case report of severe bleeding with this combination, and it may help provide insights into the risk for other patients.